2000
DOI: 10.3354/meps193191
|View full text |Cite
|
Sign up to set email alerts
|

Habitat/sex differences in time at cleaning stations and ectoparasite loads in a Caribbean reef fish

Abstract: We compared time spent at cleaning stations and ectoparasite loads for adult and subadult yellowtail damselfish Microspathodon chrysurus on nearshore fringing reefs in Barbados. In a preliminary study on 2 reefs in summer 1997, both time spent at cleaning stations and frequency of chafing were inversely correlated with distance from shore. A subsequent study in spring 1998 of fish at the shore-and seaward ends of 8 reefs revealed a strong sex by habitat association, with males predominating at the seaward end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 8 publications
5
46
1
Order By: Relevance
“…To summarise, cleaners adapt their foraging behaviour to parasite location and do remove the parasites. Assuming that monogeneans are indeed detrimental to their hosts (Thoney & Hargis 1991), our results thus support the recently growing evidence that clients benefit from cleaning interactions (Grutter 1996, 1999, Sikkel et al 2000.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…To summarise, cleaners adapt their foraging behaviour to parasite location and do remove the parasites. Assuming that monogeneans are indeed detrimental to their hosts (Thoney & Hargis 1991), our results thus support the recently growing evidence that clients benefit from cleaning interactions (Grutter 1996, 1999, Sikkel et al 2000.…”
Section: Discussionsupporting
confidence: 79%
“…More importantly, infected fish spend more time next to a cleaner behind glass than uninfected fish, and infected fish also spend more time next to a cleaner compared to a control fish than do uninfected fish (Grutter 2001). Furthermore, Gorlick (1984) and Sikkel et al (2000) found that cleaner fish clean infected client individuals longer than uninfected individuals of the same client species. What is still unknown is whether cleaners feed selectively on the parasites.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…By contrast, high densities of sponge-dwelling cleaning gobies, which feed mainly on benthic invertebrates within sponge tissue (Whiteman & C么t茅 2002), were not associated with ectoparasite emergence or client numbers. Contrary to one of our predictions, we found that higher densities of coral-dwelling cleaning gobies tended to coincide with lower gnathiid loads on their clients, at least on a small, island-wide scale (see also Sikkel et al 2000). Our prediction was based on the premise that cleaner fish are known to approach and inspect preferentially clients with high ectoparasite loads (Gorlick 1984, Grutter 1995b.…”
contrasting
confidence: 97%
“…Moreover, the maintenance of the diversity of fishes is dependent on the presence of cleaners (Grutter et al 2003), and fishes with large ectoparasite loads tend to spend more time with cleaners (Sikkel et al 2000).…”
Section: Introductionmentioning
confidence: 99%